Highly sensitive electrochemical immunosensor based on electrodeposited platinum nanostructures confined in silica nanochannels for the detection of the carcinoembryonic antigen - Guo, Qinping; Fan, Xue; Yan, Fei; Wang, Yinquan (Frontiers in Chemistry, 2023)
Herein we report a highly sensitive electrochemical immunosensor for carcinoembryonic antigen (CEA) detection based on the electrodeposited platinum nanoparticles (Pt NPs) confined in the ultrasmall nanochannels of vertically-ordered mesoporous silica film (VMSF). VMSF bearing amine groups (NH2-VMSF) can be prepared on the indium tin oxide (ITO) electrode surface via a one-step cocondensation route using electrochemically assisted self-assembly method, which renders strong electrostatic effect for [PtCl6] 2-and leads to the spatial confinement of Pt NPs inside the silica nanochannels after electrodeposition. The external surface of NH2-VMSF is functionalized with CEA antibody using glutaraldehyde as a coupling agent, resulting in an electrochemical immunosensing interface with good specificity for CEA detection. Under optimal experimental conditions, high affinity between CEA antibody and CEA produces steric hindrance effect for the accessibility of electrochemical probe ([Fe(CN)6] 3-) in the bulk solution to the underlying ITO surface, eventually resulting in the attenuated electrochemical signal and enabling the detection of CEA with a wide linear range of 0.01 pg/mL 10 ng/mL and pretty low limit of detection of 0.30 fg/mL. Owing to the signal amplification ability of Pt NPs and anti-biofouling property of NH2-VMSF, the as-prepared electrochemical immunosensor based on the Pt NPs@NH2-VMSF displays accurate analysis of CEA in human serum samples, holding great promise for health monitoring and clinical diagnosis.